Seismic Performance of an Efficient Scissor-Jack-Damper Configuration - Lihua Zhu; Pengyu Guo; Chenglong Hua; Shiyu Shan (Shock and Vibration)
Energy-dissipating or damping systems have been widely used in new and retrofitted structures for reducing earthquake damage to structural frames. Most damping devices were installed using diagonal or chevronbrace configurations, until the development of toggle-brace and scissor-jack configurations. This paper presents a modified scissor-jack-damper configuration with substantially improved efficiency. The mechanical behavior of the efficient scissor-jack-damper configuration is analyzed theoretically, and a formula for the displacement magnification factor of the configuration is proposed. A steel-frame specimen installed with the efficient scissor-jack-damper configuration was tested to verify the accuracy of the formula. The seismic responses of an uncontrolled steel-frame structure and of two controlled structures, installed with a diagonal brace and efficient scissor-jack-damper configurations, were analyzed using SAP2000. The high efficiency of the proposed scissor-jack-damper configuration is thus verified for practical engineering situations.